The Extent of Using E-Integrated Marketing Communication and its Effect on Algerian Tourism: Case Study on Algerian Tourism Agencies - Said, Rabhi; Ensaad , Redouane (Finance and Business Economies Review, 2022)
This study sought to investigate the usage profile of Electronic Integrated Marketing Communication (E-IMC) and its impact on the Performance of the Algerian tourism sector. To accomplish so, the study examines the extent to which E-IMC has been used, as well as the level of awareness, internal and external hurdles, problems, and benefits of employing it in the context of touristic marketing performance. In addition, the study had to include the characteristics of touristic agencies in terms of type, job sector, number of employees, and export experience. A mixed-method approach was utilized to study these research concerns. Following a detailed literature analysis, a speculative model of tourist market performance was developed. A questionnaire was created and given to 111 tourism agencies as part of the study. A total of 39 questioners were collected, resulting in a 35% response rate.